Risk Management of Medication Errors: Improving the Quality of Pharmacotherapeutic Practice - Richard Anthony Despott; Patricia Vella Bonanno; Charmaine Gauci (Pharmacology Research & Perspectives)
ABSTRACT A key challenge when identifying opportunities and prioritizing strategies for quality improvement of healthcare services is an accurate design specification against which clinical performance can be assessed. This study aimed to explore evidence‐based methods as a more effective framework for quality improvement in pharmacotherapeutic practices. A stakeholder management matrix was adapted to differentiate the dimensions of the theoretical construct for quality of care and establish a design specification for healthcare practice. A review of drug‐related problems (DRPs) associated with preventable medication errors was carried out on individual cases of adverse drug events (ADRs) reported in the EudraVigilance database system. The potential impact of strategies aimed at preventing the underlying root cause medication error (RCME) was evaluated according to the relative frequency and severity of patient harm identified with DRPs. Out of 1750 medication errors reported in the EudraVigilance database, 1300 cases of preventable DRPs were identified, of which 531 (41%) were classified as prescribing errors, 260 (20%) as dispensing errors, and 509 (39%) as errors encountered in drug administration. The highest risk scores were associated with case‐based prescribing errors and rule‐based drug administration errors. The research builds on a quality risk management approach to assess how targeted interventions may reduce the risk of medication errors. The theoretical model provided a basis for establishing the strategic domains of quality in health care and comparing quality improvement strategies in drug therapy. The measures required to mitigate the highest risk of error include medication review of prescribing practices, unit dose dispensing systems and in‐line quality control to avoid treatment administration errors, and patient education in dispensing practice. This framework is independent of the healthcare or institutional setting and may be applied on a broad scale for sharing best practices, harmonization of standards, and elimination of disparities in treatment outcomes.